Fractura supracondílea en el niño. Revisión del tema - Álvarez López, Alejandro; Rodríguez Rodríguez, Eugenio; Sánchez Olazábal, Lázaro; Casanova Morote, Carlos (Archivo Médico Camagüey, 2015)
Fractura supracondílea en el niño. Revisión del tema